The influence of lifestyle and social media on consumptive behavior with self-control as an intervening variable - Putry, Nur Anita Chandra; Rismawati, Rismawati (Proceeding International Conference on Accounting and Finance, 2026)
This study aims to analyze the influence of lifestyle and social media on consumptive behavior with self-control as an intervening variable. This research employs a quantitative method using primary data collected through questionnaires distributed to 104 students of the Faculty of Economics at Universitas Sarjanawiyata Tamansiswa. The data were analyzed using path analysis with IBM SPSS 26, supported by validity, reliability, and classical assumption tests. The results show that lifestyle has a negative and insignificant effect on consumptive behavior, while social media has a positive and significant effect. Lifestyle positively and significantly affects self-control, whereas social media has a negative but insignificant influence on self-control. Furthermore, self-control positively and significantly influences consumptive behavior. The findings also indicate that lifestyle has a significant indirect effect on consumptive behavior through self-control, while social media does not.